Asymmetric synthesis via stereospecific C–N and C–O bond activation of alkyl amine and alcohol derivatives. Issue 87 (4th October 2018) - Pound, Sarah M.; Watson, Mary P.
Abstract : Stereospecific, nickel-catalyzed cross-couplings of alkyl ammonium salts and carboxylates enable preparation of highly enantioenriched products with tertiary and quaternary stereocenters. Abstract : This perspective showcases our development of benzylic and allylic amine and alcohol derivatives as electrophiles for stereospecific, nickel-catalyzed cross-coupling reactions, as well as the prior art that inspired our efforts. The success of our effort has relied on the use of benzyl ammonium triflates as electrophiles for cross-couplings via C–N bond activation and benzylic and allylic carboxylates for cross-couplings via C–O bond activation. Our work, along with others' exciting discoveries, has demonstrated the potential of stereospecific, nickel-catalyzed cross-couplings of alkyl electrophiles in asymmetric synthesis, and enables efficient generation of both tertiary and quaternary stereocenters.